2018
DOI: 10.1186/s12903-018-0610-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between nutritive, non-nutritive sucking habits and primary dental occlusion

Abstract: BackgroundThe development of primary dentition can be affected by oral sucking habits. Therefore, this study aims to investigate the association of nutritive and non-nutritive sucking habits with primary dentition development.MethodsOne thousand one hundred and fourteen children aged 2 to 5 years old in Hong Kong were recruited in a cross-sectional study. Information on their nutritive (e.g. breastfeeding and bottle feeding) and non-nutritive sucking habits (e.g. pacifier use and thumb/digit sucking) was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 29 publications
5
44
0
21
Order By: Relevance
“…Continuing this comparison, there was a significant difference between G1 and G2 in both schools regarding deleterious oral habits, suggesting their importance in the installation of the malocclusion (Table 3), as observed by other authors 5,7,17,[19][20][21] by stating that the frequency, duration and intensity of non-nutritive sucking habits are determining factors for the installation of it.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Continuing this comparison, there was a significant difference between G1 and G2 in both schools regarding deleterious oral habits, suggesting their importance in the installation of the malocclusion (Table 3), as observed by other authors 5,7,17,[19][20][21] by stating that the frequency, duration and intensity of non-nutritive sucking habits are determining factors for the installation of it.…”
Section: Discussionsupporting
confidence: 73%
“…The questionnaire used in this research was previously tested and applied by Ling et al 7 to carry out an integrative review of the literature on the clinical behavior of sucking habits in children between 2 to 6 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific effect depends on the nature, onset, and duration of these habits (e.g., persistent non-nutritive sucking may result in unbalanced muscle function, hence affecting the stomatognathic system) [5]. Ling et al [6] showed that children with more than 1 year of daily pacifier use and/or thumb/digit sucking had higher risks of developing abnormal dental relationships (e.g., anterior open bite or increased overjet). A recent systematic review on pacifier sucking concluded that there is evidence that the use of a pacifier is associated with anterior open bite and posterior cross-bite, thus affecting the harmonious development of orofacial structures [7].…”
Section: Introductionmentioning
confidence: 99%
“…Existe un consenso en la literatura, que los hábitos de succión no nutritivos aumentan los factores de riesgo para maloclusiones esqueléticas, particularmente en la mordida abierta anterior (8)(9)(10)(11) . La causa presumible de mordida abierta anterior en niños con hábitos de succión es la inhibición del crecimiento vertical en la parte anterior del proceso alveolar, pero si el hábito cesa durante la fase de crecimiento, la posibilidad de corrección espontánea podría ser muy satisfactoria (12,13) .…”
Section: Discusionunclassified